(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2013)
We continue to discuss, with remarkable persistence - and now under the aegis of the imminent approval of a bill to increase the composition of the five Federal Regional Courts (TRFs) by 137 judges (more than doubling, therefore, the national number of judges), in addition to the recent approval of a PEC that creates four TRFs with the consequent (even redundant) increase in judges - the pressing issue of the notorious inefficiency of the Federal Justice system. Without, however, once again, data maxima venia, delving into the real reasons for the undeniable sluggishness of judicial provision, pointing out, as a fundamental cause, in an obvious and persistent misconception, the excessive number of cases being processed vis-à-vis the Federal Court. Translated with DeepL.com (free version)